Gene Expression Profiling Associated with Angiotensin II Type 2 Receptor-Induced Apoptosis in Human Prostate Cancer Cells - Pei, Nana (Public Library of Science, 2014)
Increased expression of angiotensin II type 2 receptor (AT2R) induces apoptosis in numerous tumor cell lines, with either Angiotensin II-dependent or Angiotensin II-independent regulation, but its molecular mechanism remains poorly understood. Here, we used PCR Array analysis to determine the gene and microRNA expression profiles in human prostate cancer cell lines transduced with AT2R recombinant adenovirus. Our results demonstrated that AT2R over expression leads to up-regulation of 6 apoptosis-related genes (TRAIL-R2, BAG3, BNIPI, HRK, Gadd45a, TP53BP2), 2 cytokine genes (IL6 and IL8) and 1 microRNA, and down-regulation of 1 apoptosis-related gene TNFSF10 and 2 cytokine genes (BMP6, BMP7) in transduced DU145 cells. HRK was identified as an up-regulated gene in AT2R-transduced PC-3 cells by real-time RT-PCR. Next, we utilized siRNAs to silence the up-regulated genes to further determine their roles on AT2R overexpression mediated apoptosis. The results showed downregulation of Gadd45a reduced the apoptotic effect by ∼30% in DU145 cells, downregulation of HRK reduced AT2R-mediated apoptosis by more than 50% in PC-3 cells, while downregulation of TRAIL-R2 enhanced AT2R-mediated apoptosis more than 4 times in DU145 cells. We also found that the effects on AT2R-mediated apoptosis caused by downregulation of Gadd45a, TRAIL-R2 and HRK were independent in activation of p38 MAPK, p44/42 MAPK and p53. Taken together, our results demonstrated that TRAIL-R2, Gadd45a and HRK may be novel target genes for further study of the mechanism of AT2R-mediated apoptosis in prostate cancer cells.